2020
DOI: 10.4103/ijcm.ijcm_349_19
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic inequalities in clustering of health-compromising behaviours among Indian adolescents

Abstract: Background: The simultaneous occurrence of health-compromising behaviors can accentuate the risk of noncommunicable diseases (NCDs). This study aimed to examine the existence and patterns of clustering of four NCD risk behaviors among adolescents and its association with social position. In addition, socioeconomic inequalities in the occurrence of clustering of NCD risk behaviors were also assessed. Methods: A cross-sectional study was undertaken among 1218 adolescents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 23 publications
4
12
4
Order By: Relevance
“…In the study it was found that females had higher odds (OR-5.51) of having at least two NCD risk factors (dyads) compared to males. This is in contrast to a recent study from north India which reported a higher prevalence of NCD risk factor dyads among males compared to females 20 . Similarly, adolescents from urban regions had higher odds of NCD risk factors and their clustering compared to rural counter parts.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In the study it was found that females had higher odds (OR-5.51) of having at least two NCD risk factors (dyads) compared to males. This is in contrast to a recent study from north India which reported a higher prevalence of NCD risk factor dyads among males compared to females 20 . Similarly, adolescents from urban regions had higher odds of NCD risk factors and their clustering compared to rural counter parts.…”
Section: Discussioncontrasting
confidence: 99%
“…A recent study from north India reported that physical inactivity and inadequate fruit and vegetable intake make up the largest of the behavioural risk factor dyads among adolescents 20 . While in our study inadequate fruit and vegetable intake, physical inactivity and consumption of packaged food were found to be strong contributors to NCD risk factor clusters, earlier studies reported obesity and overweight as predominant risk factors in NCD clusters among adolescents in north India 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Clustering of unhealthy behaviours among energy drink consumers was also apparent in both our quantitative and qualitative data results, showing that energy drink consumers had poorer quality diets, higher daily energy intake and larger BMI. Previous research has shown that multiple unhealthy behaviours cluster among young people from disadvantaged backgrounds, particularly low fruit and vegetable intake and high tobacco and alcohol use, as well as low fruit and vegetable intake and low physical activity levels coupled with high sedentary behaviour and high sugary drinks intake (35,36) . In our study, each additional SD increase in BMI was associated with 9 % greater likelihood of adolescents' consuming energy drinks.…”
Section: Comparison With Previous Researchmentioning
confidence: 99%
“…The English word "sugar" is derived from the Sanskrit word "sarkara," which signifies gravel [1]. Sugar is a ubiquitous element in many processed meals and is a major source of the energy we derive from them [2]. Particularly among young people, there has been an increase in the consumption of sugary sodas, flavored carbonated water, and juice with added sugar while milk consumption has decreased significantly [3].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the research regarding the parameters related to SSB consumption comes from high-income nations or countries that have strict policies in place to regulate the amount of sugary drinks that their citizens consume [2]. The consumption trends of SSBs among various socioeconomic and demographic categories in low-and middle-income countries such as India have only a few studies.…”
Section: Introductionmentioning
confidence: 99%